Forensic Monitoring Project Report: Gornja Grabovica Houses and Army Barracks Exhumations Federal Commission on Missing Persons - Croat Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather On 27-28 May 1998 the Federal Commission on Missing Persons - Croat Side searched a number of sites but failed to recover any human remains. Place of Exhumation: Gornja Grabovica Date of Exhumation: 27-28 May 1998 Minimum Number of Exhumed Individuals: 000